The Effect of Organic Stimulant and Inorganic Fertilizer on Two Rice Varieties (Oryza sativa L.) - Widyaswari, Erningtyas; Santosa, Mudji; Maghfoer, Moch. Dawam (Graduate School, Universitas Brawijaya, 2017)
Increased the yield of rice could be done by organic stimulant application and inorganic fertilizer, as well as the used of appropriate variety. The field experiment was aimed to study the interaction of fertilizer application and the using of variety on rice. The research was conducted at April until July 2016 in Sekarputih Hamlet, Pendem Village, Junrejo District, Batu City. This research used the Randomized Complete Block Design (RCBD) Factorial methods with 2 factors are Rice Variety (V) and Fertilizers Doses (P) with 3 replications. Cows Biourine application by dissolved 1 L biourine with 10 L water sprayed on soil and plants. EM-4 application was doing by dissolved 100 cc EM-4 with 10 L water sprayed on soil. The result of research showed that interaction of Mapan-P.05 hybrid variety (V2) added with fertilizer doses 100 kg phonska+100 kg urea+cows biourine+EM-4 (P6) can increase yield on rice in parameter 1000 grain weight to 15.29% against which added fertilizer doses 200 kg phonska+200 kg urea (P1). Keywords: Inorganic Fertilizer, Organic Stimulant, Rice, Variety.